Antibiotic Prescription Practice and Resistance Patterns of Bacterial Isolates from a Neonatal Intensive Care Unit: A Retrospective Study from Jordan - Mariam Alameri; Lobna Gharaibeh; Mervat Alsous; Aseel Yaghi; Asma’a Tanash; Saqr Sa’id; Hanan Sartawi (Antibiotics)
Background/Objectives: Neonatal sepsis is a systemic inflammation in neonates caused by bacteria, viruses, or fungi that can progress into severe conditions. In developing countries, neonatal sepsis is a major cause of mortality and a major public health issue with a high prevalence. This study aims to evaluate the antibiotic prescription practice and resistance patterns of bacterial isolates from the neonatal intensive care unit (NICU) at the largest governmental hospital in Amman, Jordan. Methods: This was a retrospective cross-sectional study. The antibiotic prescription practice and resistance patterns of bacterial isolates from the NICU at Al Basheer Government Hospital in Amman, Jordan, were evaluated. The hospital’s microbiology lab database and medical records were the sources of the retrospective data collection. Results: A total of 266 neonates treated with antibiotics were assessed. The findings showed that most neonates had late-onset sepsis (LOS) (65.4%). The penicillin group of antibiotics (ampicillin) was the most highly prescribed first empiric antibiotic for LOS and early-onset sepsis (EOS) (61.7%). Aminoglycosides (60.9%) were the most prescribed antibiotics as a second empiric treatment for EOS and LOS. The culture results showed that resistance to antibiotics was as follows: 15.4% of the culture samples were resistant to penicillin (Micrococcus and Viridans streptococci), 13.9% were resistant to cefotaxime (Klebsiella pneumoniae and Viridans streptococci), 13.2% were resistant to cefoxitin (Klebsiella pneumoniae and Staphylococcus epidermidis), and 12.4% were resistant to oxacillin (Klebsiella pneumoniae and Staphylococcus epidermidis). Conclusions: This retrospective study sheds light on the antibiotic prescription practice and resistance patterns of bacterial isolates from newborns with sepsis. The results highlight the high rates of antibiotic resistance. These findings underline the urgent need for improved antibiotic stewardship and infection control strategies to prevent resistance from spreading further.